The Canterbury Tales - Chaucer, Geoffrey, -1400; Adapted by Riley, Martin (Oxford, New York Oxford University Press, 2003)
Attempting to bring Chaucer back to life, four medieval alchemists invite a group of Chaucer's best-known pilgrims - the Knight, the Wife of Bath, the Pardoner, the Nun's Priest, and the Miller - to tell Tales. This book features activities that support the KS3 Framework for Teaching English and help students fulfil the Framework objectives.
Include Illustration
Keywords: Children's plays, English -- England--Canterbury -- Middle Ages